ANT SPECIES DIVERSITY (HYMENOPTERA, FORMICIDAE) IN THE PURWODADI BOTANICAL GARDENS, EAST JAVA, INDONESIA - Fuminori Ito; Seiki Yamane; Katsuyuki Eguchi; Woro A Noerdjito; Erniwati; Sih Kahono (Treubia, 2024)
The ant species diversity in tropical Asia has been investigated in several locations, however, these studies mainly focused on well preserved forests or plantations. The ant fauna in urban parks has only been investigated in a limited number of locations in Singapore, Hong Kong, Macao, and Indonesia. We investigated the ant fauna in the Purwodadi Botanical Gardens, East Java, and compared it to the ant fauna obtained in the Bogor Botanical Gardens. In the Purwodadi Botanical Gardens, we employed the following sampling methods that were also carried out in Bogor: (1) visual searching of ants on tree trunks, (2) visual searching of litter and top-soil ants by hand sifting (3) visual searching of ant colonies, (4) visual searching of foraging workers. In total, 109 species in 44 genera from 9 subfamilies were collected. The number of species collected from litter and soil in Purwodadi was remarkably smaller than that in Bogor, while the ant species diversity on tree trunks was similar to that of Bogor. Of the109 species, 68 were common to Bogor. Arboreal ants were more similar than ground ants between Bogor and Purwodadi.